2015
DOI: 10.1108/apjml-12-2013-0159
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing sport tourists’ revisit intentions

Abstract: Purpose – The purpose of this paper is to investigate the relationships among destination image, perceived quality, perceived value, satisfaction and revisit intention of sport tourism in Iran. Design/methodology/approach – Statistical population of this research consisted of those tourists who traveled to Mazandaran province in Iran as a sport tourism destination in 2012. A random sample of 1,250 tourists was asked to respond to questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
68
1
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 95 publications
(128 reference statements)
14
68
1
15
Order By: Relevance
“…Penelitian sebelumnya yang diadakan oleh Loureiro, dan González (2008) (Bigne et al, 2001); (C. M. Chen, Lee, Chen, & Huang, 2011). Sementara itu, (Prayag, 2009) dan (Prayag & Ryan, 2011) (Allameh, Pool, Jaberi, Salehzadeh, & Asadi, 2015) menemukan bahwa citra destinasi memiliki efek positif pada Loyalitas. (Bigne et al, 2001) telah mengungkapkan bahwa citra destinasi berhubungan langsung dengan persepsi kualitas, kepuasan dan niat untuk kembali dan kemauan merekomendasikan orang lain.…”
Section: Citra Destinasi Kepuasan Dan Loyalitasunclassified
“…Penelitian sebelumnya yang diadakan oleh Loureiro, dan González (2008) (Bigne et al, 2001); (C. M. Chen, Lee, Chen, & Huang, 2011). Sementara itu, (Prayag, 2009) dan (Prayag & Ryan, 2011) (Allameh, Pool, Jaberi, Salehzadeh, & Asadi, 2015) menemukan bahwa citra destinasi memiliki efek positif pada Loyalitas. (Bigne et al, 2001) telah mengungkapkan bahwa citra destinasi berhubungan langsung dengan persepsi kualitas, kepuasan dan niat untuk kembali dan kemauan merekomendasikan orang lain.…”
Section: Citra Destinasi Kepuasan Dan Loyalitasunclassified
“…Diversity in the conference market requires participants to weigh the cost and benefits of attending during their decision-making process [9]. Thus, the perceived value by conference participants is a crucial factor that helps examine and understand the destination's competitiveness [10]. Understanding the patterns of tourist behaviors has been the fundamental subject in the tourism sector as consumer behavior is a premise for designing marketing action.…”
Section: International Conference: Motivations and Participationsmentioning
confidence: 99%
“…The main factors motivating purchase intentions can be attitudes, evaluations and perceptions of brands. For instance, the perceived quality of a brand can improve consumers' evaluations (Wang, Li 2012;Allameh et al 2015). Chen and Chang (2008) found that brand equity and purchase intentions have a positive relationship.…”
Section: Brand Purchase Intentionsmentioning
confidence: 99%